METHODS OF IMPROVING THE EFFICIENCY OF SOLAR CELLS BY CHANGING THEIR STRUCTURE - L. O. Olimov; U.A. Axmadaliyev (American Journals Publishing, 2022)
This article analyzes the improvement of the optical properties of solar cells and the new type of pyramidal solar cell and its construction solutions. The fact that the rays of the sun falling on the surface of the element depend on the geometric dimensions and recommendations for improving the refractive index by changing them are given.
Keywords: pyramidal solar cell, refractive index, photoenergy, light absorption, construction